IL-1R and inflammasomes mediate early pulmonary protective mechanisms in respiratory brucella abortus infection - Hielpos, María Soledad (2016)
Brucella spp. infection is frequently acquired through contaminated aerosols. The role of interleukin-1 beta (IL-1β) in the early pulmonary response to respiratory Brucella infection is unknown. As shown here, IL-1β levels in lung homogenates and bronchoalveolar lavage fluid (BALF) of mice intratracheally inoculated with B. abortus were increased at 3 and 7 days p.i. At 7 days p.i., pulmonary CFU numbers were higher in IL-1 receptor (IL-1R) knockout (KO) mice than in wild type (WT) mice. At different times p.i. CFU in lungs and BALF were higher in mice lacking some inflammasome components (caspase-1, AIM2, NLRP3) than in WT mice. At 2 days p.i. pulmonary levels of IL-1b and CXCL1 (neutrophils chemoattractant) were lower in caspase-1/11 KO mice. At day 3 p.i., neutrophils counts in BALF were lower in caspase-1/11 KO mice than in WT mice. During in vitro infections, IL-1β secretion was lower in alveolar macrophages from caspase-1/11, NLRP3 or AIM2 KO mice than in WT controls. Similarly, IL-1β production by B. abortus-infected alveolar epithelial cells was reduced by pretreatment with a specific caspase-1 inhibitor. This study shows that IL-1R, probably through IL-1β action, and the NLRP3 and AIM2 inflammasomes are involved in pulmonary innate immune protective mechanisms against respiratory B. abortus infection.